Diversity of sacrifice : form and function of sacrificial practices in the ancient world and beyond - Murray, Carrie Ann, 1976- (SUNY series, The Institute for European and Mediterranean Archaeology distinguished monograph series., 2016)
"Explores sacrificial practices across a range of contexts from prehistory to the present. The term 'sacrifice' belies what is a complex and varied transhistorical and transcultural phenomenon. Bringing together scholars from such diverse fields as anthropology, archaeology, epigraphy, literature, and theology, Diversity of Sacrifice explores sacrificial practices across a range of contexts from prehistory to the present. Incorporating theory, material culture, and textual evidence, the volume seeks to consider new and divergent data related to contexts of sacrifice that can help broaden our field of vision while raising new questions. The essays contributed here move beyond reductive and simple explanations to explore complex areas of social interaction. Sacrifice plays a key role in the overlapping sacred and secular spheres for a number of societies in the past and present. How religious beliefs and practices can be integral parts of life on individual and community levels is of fundamental importance to understanding the past and present. In addition to aiding scholarly research, Diversity of Sacrifice enables students to explore this rich theme across Europe and the Mediterranean with clear discussions of theory and data"--Publisher's website